2022
DOI: 10.1007/s13592-022-00921-w
|View full text |Cite
|
Sign up to set email alerts
|

Small hive beetle, Aethina tumida (Coleoptera: Nitidulidae): chemical profile of the cuticle and possible chemical mimicry in a honeybee (Apis mellifera) pest

Abstract: The small hive beetle, Aethina tumida (Coleoptera: Nitidulidae), is an economically important pest of the Western honeybee, Apis mellifera (Hymenoptera: Apidae). We investigated the effect of rearing environment on the cuticular chemical profile of adult A. tumida, using hexane to extract the hydrocarbons and other compounds from the cuticles of beetles. Beetles were collected from A. mellifera colonies in Australia as well as reared in single sex laboratory cultures on different diets. We investigated whether… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 51 publications
0
2
0
Order By: Relevance
“…It was also found that methyl esters, ethyl palmitates and methyl linolenate extracted from cuticles of drone (Le Conte et al 1989 ) and worker larva of A. m. linguistica (Trouiller et al 1991 ) serve as pheromones and kairomones responsible for attracting the parasitic Varroa mite to the brood. The small hive beetle Aethina tumida also have the ability to detect pheromone odors from honey bees (Torto et al 2005 ) and uses chemical mimicry through cuticular hydrocarbons to masks itself in the hive (Amos et al 2022 ) and receive protein rich food from workers (Langlands et al 2021 ). In contrast, B. coeca did not show preferences for cuticular hydrocarbons but possessed the same CHC profiles, indicating that it does not use these cues for host detection, rather for camouflage within the hive (Martin and Bayfield 2014 ).…”
Section: Discussionmentioning
confidence: 99%
“…It was also found that methyl esters, ethyl palmitates and methyl linolenate extracted from cuticles of drone (Le Conte et al 1989 ) and worker larva of A. m. linguistica (Trouiller et al 1991 ) serve as pheromones and kairomones responsible for attracting the parasitic Varroa mite to the brood. The small hive beetle Aethina tumida also have the ability to detect pheromone odors from honey bees (Torto et al 2005 ) and uses chemical mimicry through cuticular hydrocarbons to masks itself in the hive (Amos et al 2022 ) and receive protein rich food from workers (Langlands et al 2021 ). In contrast, B. coeca did not show preferences for cuticular hydrocarbons but possessed the same CHC profiles, indicating that it does not use these cues for host detection, rather for camouflage within the hive (Martin and Bayfield 2014 ).…”
Section: Discussionmentioning
confidence: 99%
“…Disease-free certificates for the sale of bee packages are issued based on a thorough inspection of bee colonies. Conduct a visual inspection of the entire bee colony to detect Aethina tumida (larvae, beetles, traces of damage) (Amos et al, 2022).…”
Section: Fig 3 Life Cycle Development Of Aethina Tumidamentioning
confidence: 99%